PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X PADA MAN 2 PIDIE JAYA - Arizal Fahmi (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This study aims to determine whether the application of a jigsaw cooperative learning model can improve student learning outcomes in mathematics learning in class X MAN 2 Pidie Jaya. This type of research is quantitative research. The design of this study is planning, design, implementation, evaluation, and reporting. Data analysis was performed descriptively. The results of the data analysis showed that the acquisition of the pre-test results of students 'mathematics learning with an average of 60. Then apply the jigsaw cooperative learning model for three meetings, at the end of the lesson a post-test evaluation is given to see the students' abilities after applying the jigsaw cooperative learning model. The results of data analysis showed that the students' mathematics learning pre-test results obtained an average of 84.4. Thus it can be concluded, the jigsaw cooperative learning model can improve student learning outcomes, and the teacher always improves his skills in using the jigsaw cooperative learning model so that students are not bored and are more enthusiastic about participating in lessons and understanding mathematics learning